1997
DOI: 10.1111/jon199774242
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Leptomeningeal Hemangioblastomatosis in von Hippel‐Lindau Disease: Magnetic Resonance and Pathological Findings

Abstract: A 55-year-old man with von Hippel-Lindau disease presented with quadriparesis. Multiple enhancing cervical and thoracic spinal masses were seen on magnetic resonance imaging (MRI). A rim of diffuse, nodular enhancement linking all of the discrete masses was apparent on the surface of the cervical and thoracic regions of the cord. Surgical exploration revealed multiple extramedullary-intradural and intramedullary masses, extending to and infiltrating the cord; the leptomeninges contained numerous small tumor se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
0
20
0
2
Order By: Relevance
“…The extravasated fluid may also dissect the parenchyma in the cord and reach the central canal leading to syringomyelia. 5 Diffuse and extensive leptomeningeal infiltration by HBs similar to that in our patient is an exceedingly rare phenomenon. The term leptomeningeal hemangioblastomatosis was first introduced by Bakshi et al 5 to describe this unusual presentation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The extravasated fluid may also dissect the parenchyma in the cord and reach the central canal leading to syringomyelia. 5 Diffuse and extensive leptomeningeal infiltration by HBs similar to that in our patient is an exceedingly rare phenomenon. The term leptomeningeal hemangioblastomatosis was first introduced by Bakshi et al 5 to describe this unusual presentation.…”
Section: Discussionmentioning
confidence: 98%
“…5 Diffuse and extensive leptomeningeal infiltration by HBs similar to that in our patient is an exceedingly rare phenomenon. The term leptomeningeal hemangioblastomatosis was first introduced by Bakshi et al 5 to describe this unusual presentation. In a recent review of the literature, a total of 15 cases were reported with spinal infiltration but without supratentorial infiltration on imaging; 6 cases were associated with VHL disease and 9 caused by spontaneous mutations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Os sinais e sintomas mais frequentes são cefaléia, vômito, tontura, ataxia e distúrbios da marcha 1,[6][7][8] , sendo estes os mais referidos por nossos pacientes. A angiografia, revelando lesão altamente vascularizada em fossa posterior, bem como a ressonância nuclear magnética e tomografia axial computadorizada (Fig 1), demonstrando nódulo impregnado por contraste nesta mesma topografia, são os métodos de neuroimagem de escolha para o diagnóstico de hemangioblastomas [9][10][11] .…”
Section: Discussionunclassified